Endothelial dysfunction and carotid atherosclerosis in Malawian adults: A cross-sectional study - Joseph Kamtchum-Tatuene; Gloria Mwangalika Kachingwe; Henry C. Mwandumba; Tom Solomon; Laura A. Benjamin (eNeurologicalSci, 2020)
Background and objective: In sub-Saharan Africa, data on prevalence, risk factors and pathobiology of carotid atherosclerosis are scarce. We aimed to investigate the relationship between biomarkers of endothelial dysfunction and carotid atherosclerosis. Methods: Carotid ultrasound was performed in 66 patients. Plasma concentration of ICAM-1, PAI-1, VEGF, and soluble thrombomodulin were measured by ELISA. A univariable logistic regression analysis was performed to study the relationship between carotid atherosclerosis, biomarkers of endothelial dysfunction, and various demographic and clinical parameters of the participants. Results: The mean age of the participants was 58.7 years (95% CI: 54.4–63.1). Carotid atherosclerosis was diagnosed in 39.4% (95% CI: 27.6–52.2). In the univariable logistic regression, the following factors were associated with carotid atherosclerosis: age > 45 years (OR = 12.0, 95% CI: 1.4–98.8, p = .02), hypertension (OR = 3.8, 95% CI: 1.2–12.1, p = .02), and high-level of soluble thrombomodulin (OR = 3.4, 95% CI: 1.2–10.0, p = .02). Conclusions: There is an association between high levels of soluble thrombomodulin and carotid atherosclerosis in Malawian adults. Further studies with a larger sample size are needed to confirm our findings in other African populations.